2020
DOI: 10.1007/s00122-019-03476-0
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and successful introgression of the spring wheat-derived QTL Fhb1 for Fusarium head blight resistance in three European triticale populations

Abstract: Key message The spring wheat-derived QTL Fhb1 was successfully introgressed into triticale and resulted in significantly improved FHB resistance in the three triticale mapping populations. Abstract Fusarium head blight (FHB) is a major problem in cereal production particularly because of mycotoxin contaminations. Here we characterized the resistance to FHB in triticale breeding material harboring resistance factors from bread wheat. A highly FHB-resistant experimental line which derives from a triticale × whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 130 publications
(165 reference statements)
1
26
0
Order By: Relevance
“…In this study the broad-sense heritability estimates (H 2 ) https://doi.org/10.1371/journal.pone.0248184.g002 for agronomic traits, such as plant height and flowering time, were high whilst those for FHB associated traits (visual severity, DON accumulation) were more moderate. These broad-sense heritability estimates for both types of traits are comparable with H 2 values previously reported in the literature [38,39]. In the present study, a single FHB QTL per population was stable across environments.…”
Section: Discussionsupporting
confidence: 92%
“…In this study the broad-sense heritability estimates (H 2 ) https://doi.org/10.1371/journal.pone.0248184.g002 for agronomic traits, such as plant height and flowering time, were high whilst those for FHB associated traits (visual severity, DON accumulation) were more moderate. These broad-sense heritability estimates for both types of traits are comparable with H 2 values previously reported in the literature [38,39]. In the present study, a single FHB QTL per population was stable across environments.…”
Section: Discussionsupporting
confidence: 92%
“…In future, the development of high-throughput automatic germination scoring methods (Joosen et al 2010) could make germination analyses more costefficient and widely used for FHB resistance as well. Digital image analysis has shown promise also as an alternative to visual scorings of FHB severity in triticale (Ollier et al 2020).…”
Section: Don and Germination Capacitymentioning
confidence: 99%
“…Reliable assessment of FHB resistance has to be associated with the evaluation of kernel damage and the amount of toxins accumulated in the grain. Ollier et al [50] showed that in triticale, FHB severity symptoms on grain measured digitally as "whitened kernel surface" [51] had higher heritability coefficients than FHB symptoms on heads. This variable highly correlated with the mycotoxin content.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an attempt was made to introduce FHB resistance from the spring wheat line "CM-82036" into the triticale varieties [50,55]. The Fhb1 gene was detected and validated in triticale background.…”
Section: Discussionmentioning
confidence: 99%